Factors Accountable for Unabated Obstruction Following Pyeloplasty - Uday Sankar Chatterjee; Ashoke Kumar Basu; Debashis Mitra; Subir Kumar Chatterjee (Wolters Kluwer Medknow Publications, 2021)
Purpose: Split renal function (SFR) and frusemide washout (FWO) are assessed by the DTPA renogram to measure the renal parenchymal functions as well as the evidence of obstruction, both for diagnosis and to treat the pelviureteric junction obstruction. In good number of renal units, both these parameters remain unaltered even after surgery and cause anguish to parents and referring physicians and are usually attributed toward "defective pyeloplasty." In this study, we have tried to single out the bona fide responsible factor for the bad outcome; either the nonreversible kidney or the restenosis of pyeloplasty. Patients and Methods: We studied file of 69 patients in whom a double "J" (DJ) stent was left in situ for internal drainage for a duration of 8 weeks in the postoperative period. DTPA scans were performed preoperative, at 8 weeks with a stent in place, and at 12 and 24 months postremoval of the stent to assess renal function. Results: In our study, 45 patients (65.2%) showed improvement either in SRF or in FWO or in both after 8 weeks following pyeloplasty and 24 of 69 units (34.8%) did not show any change in renal function with DJ stent in place. Only in six units (8.7%), out of 69 units had deterioration of renal function after removal of DJ stent. Conclusions: In our opinion, no improvement of renal function found in 24 units (34.8%) even with internal drainage with DJ indicates irreversible renal damage. In 45 units (65.2%), renal function reversed after pyeloplasty and DJ stent. However, after the removal of the DJ, functions deteriorated in six units (8.7%) due to restenosis following pyeloplasties.